Incidence and risk factors contributing to exposed calvarium in the management of scalp skin cancer: a retrospective review - Brandon He; Isabella Jackson; Morgan Haines; Joseph Descallar; Quan Ngo (Australasian Journal of Plastic Surgery)
**Background:** Calvarial exposure is a recognised complication of surgical and radiotherapeutic treatment of scalp skin cancers. Exposure of the calvarium from this treatment may result in bone desiccation, infection and sequestration, which can pose significant risk to patient morbidity and mortality, and be resource-intensive to treat.